Epilepsy and brain injury: A case report of a dramatic neuropsychiatric vicious circle. (July 2013) - Rapinesi, Chiara; Del Casale, Antonio; Serata, Daniele; Kotzalidis, Giorgio D.; Scatena, Paola; Muzi, Antonio; Lazanio, Simone; Savoja, Valeria; Carbonetti, Paolo; Fensore, Claudio; Ferracuti, Stefano; Angeletti, Gloria; et al.
Abstract Primary objective: Early treatment of epilepsy is warranted to avoid possible severe consequences. This study aimed to assess the value of treatment in a patient who developed epilepsy after major brain surgery. Design: Case description. A 51 years-old man had a history of putative petit mal seizures since adolescence and left frontotemporal lobectomy after a major traffic accident at age 17. He subsequently developed quickly generalizing partial complex seizures, associated with severe behavioural alterations and personality changes; the condition was left untreated. A further seizure-related loss of consciousness led to another traffic accident at age 47. Methods and procedures: The patient was administered 200 mg/day topiramate, 600 mg/day quetiapine, 1000 mg/day valproate, 1200 mg/day gabapentin and 800 mg/day carbamazepine. Main outcomes and results: The instituted anti-epileptic treatment reduced seizure frequency and severity, but did not affect psychiatric symptomatology, which even worsened. An association between anti-epileptic drugs with mood stabilizing properties and an atypical anti-psychotic dramatically improved psychiatric symptoms, but did not prevent the patient from needing long-term healthcare. Conclusions: Long-term untreated epilepsy may expose to accident proneness and further psychiatric deterioration. Early diagnosis and treatment of epilepsy may help in avoiding a potentially lethal vicious circle.